2018
DOI: 10.1016/j.clml.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomogram for Overall Survival in Extranodal Natural Killer/T-Cell Lymphoma Patients

Abstract: Our proposed nomogram based on Eastern Cooperative Oncology Group performance status, Ann Arbor stage, albumin-to-globulin ratio, and platelet count provides an individualized risk estimate of OS in patients with ENKTL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Another possible explanation for this inconsistence was that their study with a small sample size (n = 100) may be underpowered to examine the prognostic value of CAR in ENKTL. Moreover, in keeping with previous findings in ENKTL, 9,16 the AGR, a frequently reported prognostic index which reflected the nature of both immunity and inflammation in diffuse large B-cell lymphoma, 33,34 also maintained its independent prognostic value in ENKTL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another possible explanation for this inconsistence was that their study with a small sample size (n = 100) may be underpowered to examine the prognostic value of CAR in ENKTL. Moreover, in keeping with previous findings in ENKTL, 9,16 the AGR, a frequently reported prognostic index which reflected the nature of both immunity and inflammation in diffuse large B-cell lymphoma, 33,34 also maintained its independent prognostic value in ENKTL.…”
Section: Discussionsupporting
confidence: 89%
“…1 With this regard, some researchers have found that the predictive value of these models may be further improved by other laboratory parameters (fasting blood glucose, C-reactive protein [CRP], platelet count, albumin, soluble interleukin 2 receptor, and absolute lymphocyte count). 2,7 -12…”
Section: Introductionmentioning
confidence: 99%
“…Our nomogram uses clinically significant variables that are associated with outcomes, and the final prognostic model consists of 4 clinical variables in a multivariate Cox proportional hazards model. Similar to the studies on ENKL, 4,16,17 our nomogram has provided a favorable level of predictive accuracy compared with the IPI and KPI. The C-index for the nomogram was 0.87, whereas the IPI and KPI were 0.57 and 0.59, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…However, neither an optimal treatment strategy nor a valuable prognostic index has been identified. 5,[8][9][10][11][12][13][14][15][16] Several studies have identified a few important prognostic variables and indices that predict outcomes. However, these prognostic variables and indices are rarely suitable for early stage patients who have received high-dose RT, and some of them remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation